2016
DOI: 10.1038/srep28919
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARID1A expression predicts poor survival prognosis in gastric cancer: a systematic meta-analysis from 14 studies

Abstract: The chromatin remodeling gene, AT-rich interactive domain 1A gene (ARID1A), frequently mutates inactively in gastric cancer (GC). However, its prognostic value remains controversial. To address this issue, a comprehensive meta-analysis was performed. Studies published until March 2016 were systematically searched. A total of 15 cohorts from 14 literatures involving 3183 patients were subjected to this meta-analysis. The pooled data showed that ARID1A expression loss predicted poor overall survival (OS) in GC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
(72 reference statements)
4
31
2
Order By: Relevance
“…These findings are important clues supporting the hypothesis that miR-376c is oncogenic in gastric carcinogenesis. Our in silico analysis using databases substantiated the fact that there is a low abundance of the ARID4A transcript in GC tissue and cell lines [32]. The reporter activity showed that miR-376c directly bound to the 3’-UTR of ARID4A gene and repressed the expression of luciferase gene.…”
Section: Discussionsupporting
confidence: 62%
“…These findings are important clues supporting the hypothesis that miR-376c is oncogenic in gastric carcinogenesis. Our in silico analysis using databases substantiated the fact that there is a low abundance of the ARID4A transcript in GC tissue and cell lines [32]. The reporter activity showed that miR-376c directly bound to the 3’-UTR of ARID4A gene and repressed the expression of luciferase gene.…”
Section: Discussionsupporting
confidence: 62%
“…The tumour was macroscopically dissected and DNA extraction performed using the QIAmp formalin-fixed paraffin-embedded (FFPE) tissue kit (Qiagen, Germantown, MD, USA). The regions of different SMARCA4 expression in six cases with a heterogeneous pattern (GC2, 3,6,14,21,25) were identified and sequenced separately. The targeted massively parallel sequencing was performed on the Ion GeneStudio S5 prime system using the Ion 530 chip (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: T a R G E T E D M A S S I V E L Y P A R A L L E L S E Q U E mentioning
confidence: 99%
“…4,5 Similarly, low ARID1A expression displays a higher occurrence in EBV and MSI-associated GC and a positive correlation with advanced stage and poor prognosis. 6,7 Yamamichi et al demonstrated that decreased SMARCA2 expression occurred in 37 of 89 cases (42%) and more frequently in papillary or moderately to poorly differentiated adenocarcinoma. 8 Recently, SMARCA4 deficiency was shown to be a pivotal cause of several aggressive tumours, including small-cell carcinoma of the ovary, hypercalcaemic type (SCCOHT), and undifferentiated sarcoma or carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 Since ARID1A is considered a tumor suppressor, loss of ARID1A protein has been indicated as a poor prognostic factor in GCs. 10 Recent transcriptomic and clinical studies have revealed that GCs with MSI-H or Epstein-Barr virus (EBV) have higher PD-L1 expression. 8,11 In a recent clinical trial, these two subtypes of GCs have shown much better response rates to PD-1 inhibition.…”
Section: Introductionmentioning
confidence: 99%